Biomarkers of Drug-Induced Kidney Toxicity. Issue 2 (April 2019) - Griffin, Benjamin R.; Faubel, Sarah; Edelstein, Charles L.
Abstract : Abstract: Blood urea nitrogen and serum creatinine are imperfect markers of kidney function because they are influenced by many renal and nonrenal factors independent of kidney function. A biomarker that is released directly into the blood or urine by the kidney in response to injury may be a better early marker of drug-induced kidney toxicity than blood urea nitrogen and serum creatinine. Urine albumin and urine protein, as well as urinary markers kidney injury molecule-1 (KIM-1), β2-microglobulin (B2M), cystatin C, clusterin, and trefoil factor-3 (TFF-3) have been accepted by the Food and Drug Administration and European Medicines Agency as highly sensitive and specific urinary biomarkers to monitor drug-induced kidney injury in preclinical studies and on a case-by-case basis in clinical trials. Other biomarkers of drug-induced kidney toxicity that have been detected in the urine of rodents or patients include IL-18, neutrophil gelatinase-associated lipocalin, netrin-1, liver-type fatty acid–binding protein (L-FABP), urinary exosomes, and TIMP2 (insulin-like growth factor–binding protein 7)/IGFBP7 (insulin-like growth factor–binding protein 7), also known as NephroCheck, the first Food and Drug Administration–approved biomarker testing platform to detect acute kidney injury in patients. In the future, a combined use of functional and damage markers may advance the field of biomarkers of drug-induced kidney toxicity. Earlier detection of drug-induced kidney toxicity with a kidney-specific biomarker may result in the avoidance of nephrotoxic agents in clinical studies and may allow for earlier intervention to repair damaged kidneys.